High-temperature behavior and mechanical characteristics of boron waste additive metakaolin based geopolymer composites reinforced with synthetic fibers - Celik, Abdullah; Yilmaz, Kemalettin; Canpolat, Orhan; Al-Mashhadani, Mukhallad M.; Aygormez, Yurdakul; Uysal, Mucteba (ELSEVIER SCI LTD, 2018)
This paper aims to examine high-temperature behavior and some mechanical and microstructural characteristics of boron waste additive metakaolin based geopolymer mortar composites reinforced with four various fiber types. Synthetic fibers (polyolefin, basalt, modified polyamide and polyvinyl alcohol) were used to evaluate their addition effect on the geopolymer composites behavior. Some experimental tests were performed such as compressive strength, flexural strength, toughness, abrasion resistance and high-temperature exposure to determine the influence of the fibers to be added on the properties of metakaolin based geopolymer mortars. Geopolymer mixtures were prepared by a combination of boron waste and metakaolin activated by sodium hydroxide and sodium silicate solutions and then heat cure was done. Experimental test results indicated that the addition of various types of fibers improved the strength characteristics of the geopolymer composites, for instance, PVA fiber samples yielded a flexural toughness improvement of 415.58% with respect to control sample. Concerning abrasion resistance, all of the manufactured samples showed a length change of less than 2 mm and a weight loss of less than 15 g. The use of synthetic fibers positively affected high-temperature behavior of metakaolin based geopolymer composites in terms of strength loss, weight loss and UPV loss. The microstructural analysis revealed an acceptable degree of bonding between synthetic fibers and geopolymeric matrix. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Geopolymer; Metakaolin; Boron waste; Synthetic fibers; High temperature; Abrasion resistance; FLY-ASH; BASALT FIBER; BOTTOM ASH; CONCRETE; STRENGTH; CEMENT; COLEMANITE; FRACTURE; TOUGHNESS; Construction & Building Technology; Engineering; Materials Science